Mycoplasma phosphoenolpyruvate-dependent sugar phosphotransferase system: glucose-negative mutant and regulation of intracellular cyclic AMP. - Mugharbil, U (1978)
Glucose-negative mutants of Mycoplasma capricolum were selected for growth on fructose in the presence of the toxic glucose analog alpha-methyl-D-glucopyranoside. The mutants are defective in the phosphoenolpyruvate:sugar phosphotransferase system for glucose. One mutant, pts-4, was studied in detail. It lacks the glucose-specific, membrane-bound enzyme II, IIGlc, as well as the general, low-molecular-weight, phosphocarrier protein, HPr. In place of the latter, however, it has a fructose-specific protein, HPrFru. Consistent with these changes, the mutant lost the ability to grow on glucosamine and maltose but retained its ability to grow on sucrose. In the glucose-negative mutant, glucose did not regulate the intracellular concentration of cyclic AMP. The intracellular concentration of cyclic AMP in M. capricolum is regulated by the presence of metabolizable sugars. In the wild-type, both glucose and fructose reduced the intracellular concentration of cyclic AMP; however, in the glucose-negative mutant, glucose no longer regulated the intracellular level of cyclic AMP.